Development and Assessment of an Online, Asynchronous State-Specific Pharmacy Law Continuing Education Program for Multistate Pharmacy Jurisprudence Examination Preparation - Apryl Peddi; Lauren Caldas; Evan Sisson; Sofia Yousufzai; Laura Frankart (INNOVATIONS in Pharmacy)
Description of the Problem: The Multistate Pharmacy Jurisprudence Examination (MPJE) is a licensure requirement for pharmacists. National pass rates for this exam are variable and have recently been decreasing nationally. Current support for graduates in pharmacy law courses and MPJE test preparation tools varies between states and institutions.